Age at menopause and lifetime cognition: Findings from a British birth cohort study. (8th May 2018) - Kuh, Diana; Cooper, Rachel; Moore, Adam; Richards, Marcus; Hardy, Rebecca
Abstract : Objective: We investigated whether cognitive performance between ages 43 and 69 years was associated with timing of menopause, controlling for hormone replacement therapy, childhood cognitive ability, and sociobehavioral factors. Methods: We used data from 1, 315 women participating in the Medical Research Council National Survey of Health and Development (a British birth cohort study) with known age at period cessation and up to 4 assessments of verbal memory (word-learning task) and processing speed (letter-cancellation task) at ages 43, 53, 60–64, and 69. We fitted multilevel models with linear and quadratic age terms, stratified by natural or surgical menopause, and adjusted for hormone replacement therapy, body mass index, smoking, occupational class, education, and childhood cognitive ability. Results: Verbal memory increased with later age at natural menopause (0.17 words per year, 95% confidence interval [CI]: 0.07–0.27, p = 0.001); an association remained, albeit attenuated, after full adjustment (0.09, 95% CI: 0.02–0.17, p = 0.013). Verbal memory also increased with later age at surgical menopause (0.16, 95% CI: 0.06–0.27, p = 0.002), but this association was fully attenuated after adjustment. Search speed was not associated with age at menopause. Conclusion: Our findings suggest lifelong hormonal processes, not just short-term fluctuations during the menopause transition, may be associated with verbal memory, consistent with evidence from a variety of neurobiological studies; mechanisms are likely to involve estrogen receptor β function. Further follow-up is required to assess fully the clinical significance of these associations.